Differential effect of ambient air pollution exposure on risk of gestational hypertension and preeclampsia - Nobles, Carrie J. (Hypertension, 2019)
Although ambient air pollution may increase hypertension risk through endothelial damage and oxidative stress, evidence is inconsistent regarding its effect on hypertension in pregnancy. Prior research has evaluated a limited scope of pollution species and often not differentiated preeclampsia, which may have a placental origin, from gestational hypertension. Among 49,607 women with at least two singleton deliveries in the NICHD Consecutive Pregnancies Study (2002–2010), we estimated criteria pollutant and volatile organic compound (VOC) levels during pregnancy using Community Multiscale Air Quality models and abstracted gestational hypertension and preeclampsia diagnoses from medical records. Generalized estimating equations accounted for repeat pregnancies and adjusted for ambient temperature and maternal age, race/ethnicity, BMI, smoking, alcohol, parity, insurance, marital status and asthma. Air pollution levels were low to moderate (e.g. median 41.6 (interquartile range 38.9–43.7) ppb for ozone and 35.1 (28.9–40.3) ppb for nitrogen oxides). Higher levels of most criteria pollutants during preconception and the first trimester were associated with lower preeclampsia risk, while higher second trimester levels were associated with greater gestational hypertension risk. For example, an interquartile increase in first trimester carbon monoxide was associated with a relative risk of 0.88 (95% CI 0.81–0.95) for preeclampsia and second trimester carbon monoxide a relative risk of 1.14 (95% CI 1.07–1.22) for gestational hypertension. VOCs, conversely, were not associated with gestational hypertension but consistently associated with higher preeclampsia risk. These findings further suggest air pollution may affect the development of hypertension in pregnancy, although differing etiologies of preeclampsia and gestational hypertension may alter these relationships.